The effect of sleep hygiene education and relaxation exercises on insomnia among postmenopausal women: A randomized clinical trial. Issue 4 (23rd March 2018) - Duman, Mesude; Timur Taşhan, Sermin
Abstract: Aim: This study used a randomized controlled trial model to determine the effect of progressive relaxation exercises and sleep hygiene training given to postmenopausal women with insomnia. Methods: A total of 161 postmenopausal women with insomnia were recruited and randomly assigned to experimental (n = 81) and control (n = 80) groups. The experimental group received sleep hygiene and progressive relaxation exercise training, but the control group only received routine health care. The relaxation exercise training was repeated once a week for 8 weeks. The study determined the effect of the intervention on insomnia symptoms. The data were collected between 15 June and 15 September 2015 and evaluated using descriptive statistics, independent samples t ‐test, chi‐squared test, and Cronbach alpha analysis. Results: The mean (SD) score of the experimental group on the Women's Health Initiative Insomnia Rating Scale was 14.03 (3.4) pretest and 7.09 (3.4) posttest. The difference between the pretest and posttest scores was statistically significant ( P < .001), as was the difference between the rates of insomnia symptoms between the groups posttest ( P < .001). Conclusion: The findings of study suggest that nurses teaching progressive relaxation exercises and sleep hygiene would benefit postmenopausal women who suffer from insomnia. SUMMARY STATEMENT: What is already known about this topic? Insomnia is an extensive and common problem among postmenopausal women. Previous studies suggest using nonpharmacological methods to reduce insomnia symptoms. The studies on insomnia suggest that multiple, rather than single, nonpharmacological methods should be used to treat insomnia. No studies have tested sleep hygiene education and progressive relaxation exercises for insomnia among postmenopausal women. What this paper adds? This first research in Turkey on treating insomnia symptoms in postmenopausal women showed that sleep hygiene education and progressive relaxation exercises are effective as nonpharmacological techniques for reducing postmenopausal women's insomnia symptoms. Sleep hygiene education and progressive relaxation exercises are a simple, safe, and cost‐effective intervention that is suitable for postmenopausal women to practice at home by following instructions on a compact disc. Health care professionals can easily provide this intervention to postmenopausal women. The implications of this paper: Study findings support education of postmenopausal women on sleep hygiene and an appropriate guide for this was created. The findings promote the inclusion of progressive relaxation exercise, a nonpharmacological method, in nursing care. This type of intervention may be useful in developing and middle‐income countries with limited monetary and trained labour resources.